Rasionalitas Masyarakat Samin dalam Melaksanakan Tradisi TolakBala di Masa Pandemi COVID-19 - ., Novianti (Paradigma, 2022)
Abstract The tradition of rejecting reinforcements or gemblang is an activity carried out by the Samin community in the Japanese hamlet. The tradition is carried out from generation to generation and carried out at a certain time. This tradition is carried out once a year by the Samin community. Like during the pandemic, the Samin community has its own strategy to deal with it, namely by carrying out the tradition of rejecting reinforcements. There is a change in the meaning and purpose of the implementation of repulsion before and during the pandemic, when the pandemic is aimed at minimizing the spread of covid-19 in the Japanese Hamlet and asking for a better life. Whereas before the pandemic, the tradition of rejecting reinforcements was interpreted as a form of gratitude for being given an abundant harvest. As for the uborampe used when the pandemic is different, there is an additional cone and the implementation is simpler. The actions taken by the Samin community are certainly contrary to government regulations during the pandemic. Even so, the Samin community still maintains the existing tradition because it is believed to have a positive impact on life. The formulation of the problem in this study is how the rationality of the actions of the Samin community in carrying out the tradition of rejecting reinforcements during the pandemic. The aims of this research are 1). To find out the views of the Samin community regarding the Covid-19 Pandemic 2). To identify before and after the implementation of the tradition of rejecting reinforcements 3). To analyze the rationality of the Samin community in carrying out the tradition of rejecting reinforcements during the pandemic. This study uses a qualitative research with an ethnomethodological approach. Using the perspective of social action theory proposed by Max Weber. The research location is in the Japanese Hamlet of Margomulyo Bojonegoro. The results of the study stated that there were 3 actions taken, namely traditional actions, value-oriented actions and affective actions. Keywords: Rationality, Society, Tradition of rejecting reinforcements